Prognosis of 1169 hepatitis C chronically infected patients with decompensated cirrhosis in the predirect‐acting antiviral era. Issue 4 (25th November 2016) - McDonald, S. A.; Innes, H. A.; Aspinall, E.; Hayes, P. C.; Alavi, M.; Valerio, H.; Goldberg, D. J.; Hutchinson, S. J.
Summary: At a population level, little is known regarding the risk of liver‐ and nonliver‐related mortality and hospitalization and the development of hepatocellular carcinoma (HCC) in hepatitis C virus (HCV)‐infected patients with decompensated cirrhosis (DC). This large‐scale national record‐linkage study estimates these outcomes following first hospital admission for DC. Record‐linkages between national HCV diagnosis and clinical databases and the national inpatient hospital episode database and mortality register were conducted to follow‐up the disease course of all identified HCV‐diagnosed and chronically infected persons. The study population consisted of 1169 HCV chronically infected persons who had a first hospital admission for DC within the period 1994‐2013. We observed an overall average annual percentage change of 12.6% in new DC patients (from 63 in 1994‐1999 to 541 in 2009‐2013), with no evidence for any improvement in the relative risks of liver‐related or all‐cause death over time. Between 1 January 1994 and 31 May 2014, 722 and 95 DC patients had died of a liver‐ and a nonliver‐related cause, respectively, and 106 patients had a subsequent first admission for HCC. The 5‐year cumulative incidence of liver‐related mortality, nonliver‐related mortality and first subsequent HCC admission was 61.3%, 8.2% and 8.8%, respectively. The health burden in HCV‐infected patients associated with development of decompensated cirrhosis has increased dramatically over the last 20 years. Our findings establish the baseline mortality and HCC progression rates in DC patients against which the impact of new antiviral therapies can be measured.